Effect of Limb Position at the Time of Skin Marker Application on Sagittal Plane Kinematics of the Dog - Kim, Sun-Young; Torres, Bryan T.; Sandberg, Gabriella S.; Budsberg, Steven C. (Veterinary and Comparative Orthopaedics and Traumatology, 2017)
Objectives To evaluate the effect of limb position during initial skin marker application on sagittal plane kinematics of the hindlimb.Methods Six healthy dogs (20–30 kg) were evaluated. An established two-dimensional kinematic model of the pelvic limb was utilized to describe sagittal plane motion. Kinematic markers were applied separately for each dog while standing in three different positions: (1) the limb extended cranially, (2) a normal standing limb position and (3) the limb extended caudally. Following marker application at each of the three positions, dynamic gait was recorded at a walk (velocity, 0.9–1.2 m/s; acceleration, 0.5m/s2). Five valid trials were used for comparison. Complete waveform analysis was performed with generalized indicator function analysis (GIFA). Maximum and minimum joint angles and joint range of motion were compared with a one-way repeated measures ANOVA with significance at p < 0.05.Results Significant differences were found between stifle waveforms. No differences were found between the hip or tarsus waveforms. Minimum and maximum joint angles were significantly different for the hip and stifle but not for the tarsus. No differences were found between ranges of motion for any joint evaluated.Clinical Significance Limb position at the time of skin marker application affects gait data and is an important consideration for kinematic analysis of the hindlimb in dogs.
Keywords: kinematics; dog; variability